2019
DOI: 10.13189/ujer.2019.071801
|View full text |Cite
|
Sign up to set email alerts
|

Creating an Effective Form of Communication Strategy in Foreign Language Learning

Abstract: The present article is devoted to creating an effective form of communication strategy within the process of teaching a foreign language (FL) and providing a means of stimulating cognitive interest, motivation, as well as cognitive-practical independence among students in the process of mastering an FL. On the basis of the given analysis, it is concluded that communicative learning strategies can develop critical thinking in students by reason of the problematic nature of educational tasks and consequently cre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 2 publications
1
0
0
Order By: Relevance
“…Furthermore, this study supported earlier research that suggested educators of secondlanguage essay writing should employ more genuine and authentic writing activities to help students develop their critical thinking competencies and comprehension of diverse contextual linguistic elements (Shemshurenko et al, 2019). In addition, the teaching methods are crucial for developing Chinese school students' critical Malay essay-writing competencies.…”
Section: Discussionsupporting
confidence: 82%
“…Furthermore, this study supported earlier research that suggested educators of secondlanguage essay writing should employ more genuine and authentic writing activities to help students develop their critical thinking competencies and comprehension of diverse contextual linguistic elements (Shemshurenko et al, 2019). In addition, the teaching methods are crucial for developing Chinese school students' critical Malay essay-writing competencies.…”
Section: Discussionsupporting
confidence: 82%